Regional Impact Analyses and the Appropriate Treatment of public budget constraints under devolution: An application to Scottish Higher Education Institutions (HEIs) - Kristinn Hermannsson; Katerina Lisenkova; Peter G McGregor; J Kim Swales (European Regional Science Association (ERSA), 2010)
There have been numerous studies of the "impact" of HEIs on their host regions. These have typically focused on the demand for goods and services in the host region. The best of these studies employ regional input-output analyses. However, there has developed a "policy scepticism" about the value of such analysis based on notions of either demand-side (binding budget constraints) or supply-side (binding resource constraints) "crowding out", to the point where the demand side impact of HEIs is regarded as negligible. In this paper we provide a systematic critique of this policy scepticism. While we reject the extreme form of policy skepticism we do acknowledge the importance of binding public sector budget constraints under devolution, and argue that such constraints should be accommodated in future impact studies. We focus our own impact analysis on the HEI sector's impact net of its public income by simulating the effect of switching public expenditure funds between HEIs and other activities using a modified HEI-disaggregated input-output model of Scotland. The results suggest that conventional impact studies do overestimate the impact of HEIs, but importantly that the policy scepticism that treats the demand-side impact of HEIs neglects some important impacts of these institutions, in particular their export intensity.
Keywords: R51; R15; H75; I23; 330; Higher education; Input-Output; Scotland; Impact study; Multipliers; Devolution